2011
DOI: 10.3892/ijo.2011.1321
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox gene expression profile indicates HOXA5 as a candidate prognostic marker in oral squamous cell carcinoma

Abstract: The search for molecular markers to improve diagnosis, individualize treatment and predict behavior of tumors has been the focus of several studies. This study aimed to analyze homeobox gene expression profile in oral squamous cell carcinoma (OSCC) as well as to investigate whether some of these genes are relevant molecular markers of prognosis and/or tumor aggressiveness. Homeobox gene expression levels were assessed by microarrays and qRT-PCR in OSCC tissues and adjacent non-cancerous matched tissues (margin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 47 publications
0
21
0
5
Order By: Relevance
“…This clinical evolution diversity probably occurs due to multiple steps that unchain HNSCC, in which genetic events lead to the disruption of normal pathways, followed by clonal evolution. Some genes already have their role established in carcinogenesis, although the comprehension of other combined pathways could reflect in the establishment of new drug therapies and in improvement of the treatment effectiveness . With the accumulation of large amount of human gene expression data, it is possible, and also cost‐effective, to use the already available data for identifying new tumor markers or therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This clinical evolution diversity probably occurs due to multiple steps that unchain HNSCC, in which genetic events lead to the disruption of normal pathways, followed by clonal evolution. Some genes already have their role established in carcinogenesis, although the comprehension of other combined pathways could reflect in the establishment of new drug therapies and in improvement of the treatment effectiveness . With the accumulation of large amount of human gene expression data, it is possible, and also cost‐effective, to use the already available data for identifying new tumor markers or therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Some genes already have their role established in carcinogenesis, although the comprehension of other combined pathways could reflect in the establishment of new drug therapies and in improvement of the treatment effectiveness. [14][15][16] With the accumulation of large amount of human gene expression data, it is possible, and also cost-effective, to use the already available data for identifying new tumor markers or therapeutic targets. However, with the availability of data from different platforms, it is worth investigating how the expression measurements produced from different technologies should be compared and integrated if possible.…”
Section: Discussionmentioning
confidence: 99%
“…OCT-4 is a homeobox gene well known for its function in generating induced pluripotent stem cells (Bhartiya, 2013;Seiler et al, 2011); this gene has also been identified as an oncogene known for promoting the features of cancer stem cells (Li et al, 2017;Phiboonchaiyanan & Chanvorachote, 2017). In addition to OCT-4, an increasing body of evidence reveals that homeobox genes may participate in the promotion of various malignant phenotypes such as the proliferation, migration and invasion of cancers (Hirao et al, 2019;Miwa & Kanda, 2019;Rodini et al, 2012;Song et al, 2019). We have previously reported that HoxC6, another member of homeobox superfamily, functions as an oncogene in ESCC (Tang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A partir dos resultados obtidos, aqueles genes com expressão alterada poderão ser futuramente utilizados como marcadores específicos para uma doença, bem como para uso de alvos terapêuticos ou no desenvolvimento de vacinas (33,34) , no entanto embora esta ferramenta seja extremamente abrangente e eficaz na identificação de uma grande quantidade de genes, este não é o ponto crítico a ser desvendado, mas sim a informação quantitativa associada com um dado perfil de expressão (34) . Sendo assim, a expressão dos genes identificados por array deve ser validada com metodologias complementares, como a RT-PCR convencional, ou ainda, em tempo real (qRT-PCR), possibilitando a quantificação dessa expressão (35) . (35) .…”
Section: Técnicas De Análise Molecularunclassified
“…Sendo assim, a expressão dos genes identificados por array deve ser validada com metodologias complementares, como a RT-PCR convencional, ou ainda, em tempo real (qRT-PCR), possibilitando a quantificação dessa expressão (35) . (35) .…”
Section: Técnicas De Análise Molecularunclassified